2013
DOI: 10.1093/geront/gnt010
|View full text |Cite
|
Sign up to set email alerts
|

Recession and Expected Retirement Age: Another Look at the Evidence

Abstract: As the baby boom cohorts approach retirement age, it will be important to better understand how workers consider macro factors such as the state of the economy and firm-level factors and personal finances when planning for retirement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 28 publications
0
43
1
Order By: Relevance
“…In addition, it allows a valuable evaluation of current retirement reforms that have not yet affected current pensioners to the full extent due to the time-lagged character of the pension systems reforms, for example, regarding the stepwise increase of the official retirement age in Germany. Hofäcker [33] [17], Sweden [16], the United States [36,37], and Australia [37] support this assumption, as they find an increase in the planned retirement age after reforms of the pensions system and the labor market. I expect a similar development in Germany also for the longer observational period, since the changes of the pension system cannot be attributed to one single reform but to several reforms which started in the beginning of the 1990s and lasted until the end of the 2010s, as described in the previous chapter.…”
Section: Expected Retirement Age In Germanymentioning
confidence: 99%
“…In addition, it allows a valuable evaluation of current retirement reforms that have not yet affected current pensioners to the full extent due to the time-lagged character of the pension systems reforms, for example, regarding the stepwise increase of the official retirement age in Germany. Hofäcker [33] [17], Sweden [16], the United States [36,37], and Australia [37] support this assumption, as they find an increase in the planned retirement age after reforms of the pensions system and the labor market. I expect a similar development in Germany also for the longer observational period, since the changes of the pension system cannot be attributed to one single reform but to several reforms which started in the beginning of the 1990s and lasted until the end of the 2010s, as described in the previous chapter.…”
Section: Expected Retirement Age In Germanymentioning
confidence: 99%
“…Moreover, baby boomers experienced decreases in wealth from sources such as the stock and housing markets, and increases in late‐life debt following the 2008 recession [Mann, ; McFall, ; Szinovacz et al, , ; Ondrich and Falevich, ]. Using pre‐ and post‐crash surveys from the Cognitive Economics study, McFall [] found that the average wealth loss between July 2008 and May/June 2009 was associated with an increase in the average planned retirement age of approximately 2.5 months.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in housing values did not influence retirement expectations. Szinovacz, Martin, and Davey (2013) reporting on the same HRS questions about the probability of working past age 62 or 65 also found small effects of changes in the DJIA and in occupational unemployment rates, especially among workers who are older, closer to retirement, and among those with low or high education. Our analyses complement these earlier studies by addressing changes in retirement plans and expected retirement age linked to specific plans.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 86%